Aging and Rheological Properties of Latex and Crumb Rubber Modified Bitumen Using Dynamic Shear Rheometer - Abdulnaser M Al-Sabaeei; Bayu Agus Mustofa; Muslich Hartadi Sutanto; Sri Sunarjono; Nura Bala (Journal of Engineering and Technological Sciences, 2020)
Rubberized bitumen technology has been applied for a long time to enhance the performance of the asphalt pavement. In this research, the influence of natural rubber (NR) latex and crumb rubber (CR) on the conventional and rheological characteristics of 80/100 penetration grade bitumen before and after aging was compared. Conventional tests of penetration, ring and ball temperature, and ductility were conducted to evaluate the consistency of base bitumen and rubberized bitumen. A dynamic shear rheometer (DSR) test was carried out to evaluate the viscoelastic characteristics of the base and rubberized bitumen. The results showed that the addition of NR latex and CR reduced the penetration grade and increased the ring and ball temperature and ductility of the rubberized bitumen. This indicates that promising enhancement of the bitumen properties can be expected with the addition of NR latex and CR. The rheological properties analysis results showed that addition of CR up to 8% and NR latex up to 4% improved the complex modulus and rutting resistance of the rubberized bitumen compared to conventional bitumen. This indicates that the application of NR latex and CR in bitumen modification is expected to improve the durability of asphalt pavement.